THE EFFECT OF WORK DISCIPLINE, WORK MOTIVATION, EMPLOYEE COMMITMENT AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE IN PUBLIC WORKS AND SPACE PLANNING IN KARIMUN REGENCY - Syahril, Syahril; Khaddafi, Muammar; Hutasoit, Hasudungan; Andykhatria, Andykhatria; Almansa Fitra, Mohamad; Wayan Catra Yasa, I (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine: (1) the influence of work discipline on employee performance at the Public Works and Spatial Planning Office of Karimun Regency, (2) the influence of work motivation on employee performance at the Public Works and Spatial Planning Office of Karimun Regency, (3) the influence of employee commitment on employee performance at the Public Works and Spatial Planning Office of Karimun Regency, (4) the influence of work experience on employee performance at the Public Works and Spatial Planning Office of Karimun Regency, (5) the influence of work discipline on work motivation at the Public Works and Spatial Planning Office of Karimun Regency, (6) the influence of work discipline on employee commitment at the Public Works and Spatial Planning Office of Karimun Regency, (7) the influence of work discipline on work experience at the Public Works and Spatial Planning Office of Karimun Regency, (8) the influence of work motivation on employee commitment at the Public Works and Spatial Planning Office of Karimun Regency, (9) the influence of work motivation on work experience at the Public Works and Spatial Planning Office of Karimun Regency, (10) the influence of employee commitment to work experience at the Public Works and Spatial Planning Office of Karimun Regency, (11) the influence of work discipline, work motivation, employee commitment and work experience on employee performance at the Public Works and Spatial Planning Office of Karimun Regency, (12) the influence of work discipline on work motivation through the performance of employees at the Public Works and Spatial Planning Office of Karimun Regency. This research uses quantitative research with associative methods. The data collection techniques in this study were questionnaires and interviews. The sampling technique used was probability sampling technique, namely stratified random sampling in the Public Works and Spatial Planning Office of Karimun Regency with a total of 66 respondents. The validity and reliability of the questionnaire data have been tested.